STABILITY AND SOLUBILITY OF ARSENOPYRITE, FEASS, IN CRUSTAL FLUIDS - Pokrovski G.S.; Kara S.; Roux J. (My University, 2002)
The stability and solubility of natural arsenopyrite (FeAsS) in pure water and moderately acid to slightly basic aqueous solutions buffered or not with H2 and/or H2S were studied at temperatures from 300 to 450°C and pressures from 100 to 1000 bar. The solubilities of FeAsS in pure water and dilute HCl/NaOH solutions without buffering are consistent with the formation of the As(OH)3⁰(aq) species and precipitation of magnetite. At more acid pH (pH ≤2), arsenopyrite dissolves either stoichiometrically or with formation of the As-FeAsS assemblage. In H2S-rich and H2-rich aqueous solutions, arsenopyrite dissolution results in the formation of pyrrhotite (±pyrite) and iron arsenide(s), respectively, which form stable assemblages with arsenopyrite.